Climate and Human-Driven Variability of Summer Hypoxia on a Large River-Dominated Shelf as Revealed by a Hypoxia Index - Wang, Kui; Cai, Wei-Jun; Chen, Jianfang; Kirchman, David; Wang, Bin; Fan, Wei; Huang, Daji (Frontiers in Marine Science, 2021)
Coastal hypoxia has become common especially in large river dominated coastal ecosystems. For better quantifying the severity of hypoxia and the contribution of hypoxia drivers, we applied principal component analysis (PCA) on observable properties from eight summer hypoxia events in the East China Sea and defined the first principal component as the hypoxia index (HI). Multiple linear regression showed that the HI significantly correlated with three direct hypoxia drivers including water column stratification, subsurface water residence time, and respiration rate, which accounted for 5.7%, 55.3% and 34.5% respectively, of the total variance of PCA derived HI. We further reconstructed the HI over the past 60 years using available long-term data of stratification, model-derived residence times and respiration rates. The results show that summer hypoxia has become more severe since 1960s. ENSO and global warming may have exacerbated hypoxia through affecting the river discharge, resulting in freshening in the plume-impacted shelf area, while anthropogenic activities may have exacerbated hypoxia through elevating fluvial nutrient concentrations, resulting in higher respiration rate. In addition, warming of the bottom water originated from Kuroshio Current accounts for an additional increasing rate for HI, which made hypoxia more severe by means of decreasing oxygen solubility. Overall, our results indicate that stratification, water residence and oxygen solubility resulting from climate change can explain about 80% while higher respiration resulting from higher nutrient inputs can explain about 20% of the variation in the severity of hypoxia during the past half century.